PENGANTAR ILMU HUKUM DALAM PENGGUNAAN INTERNET - Ni Kadek Astrina Desiana (Jurnal Ilmu Hukum Sui Generis, 2021)
The use of the internet is very important for the community, but in its application in Indonesia, rural areas have become areas with low internet distribution, this problem has resulted in many rural communities being unable to adapt to the internet, which results in rural communities not being able to use the internet properly. This problem is felt by approximately 45% of the Indonesian population, most of whom are residents or people in rural areas (3T) Indonesia. . In this study using qualitative research methods by focusing on the problem of the spread of the internet in rural areas in law of internet.